Genotoxicidad De Fenitoina En Eritrocitos Polipromaticos De Rattus Novergicus Cepa Holtzman. - Eustaquio Tuestas, Angela Esmeralda (2015)
The study aimed to demostrate the genotoxicity of phenytoin in polychromatic erythrocytes (PCE) of Rattus norvegicus strain Holtzman, though using micronucleus test. Five groups of five specimens each one were established, a negative control group (SSF), three experimental groups treated with phenytoin (5, 7.5 and 10 mg / kg BW), treaments for these groups were intraperitoneally during 14 days; a positive control group treated with cyclophosphamide (50 mg/kg BW) intraperotineally for 24 hours. Micronucleated PCE frequency in a total of 2000 per animal wes determined. The results show significative increase in genotoxcicity rate of phenytoin (4.62 ± 0.54, 5.39 ± 0.43, 5.49 ± 0.41) and cyclophosphamide (8.18 ± 0.29) compared to negative control group (0.08 ± 0.15); significative increase in the frequency of micronucleated EPC in individuals treated with phenytoin (92.4 ± 10.89, 8.52 ± 107.8, 109.8 ± 8.11) and cyclophosphamide (163.6 ± 5.77), in proportion to negative control group (1.6 ± 3.05) was evident, it was observed variation in the size and number of micronucleus. It was concluded that phenytoin has genotoxic effect, reflected in the presence of high frequency of micronucleated PCE.